The Positive Impact of Organizational Trust: a Systematic Review - Idha Rahayuningsih (Universitas Ahmad Dahlan, 2019)
The critical role of trust is to strengthen working relationships to ensure that organizations achieve their goals effectively. This study aims to explore the positive impact of organizational trust, namely trust towards colleagues, employers, and organization. We conducted a systematic review following the PRISMA guideline, highlighting the number of records that were identified, screened, assessed for eligibility, and included for the study. The literature search was conducted online by using the keyword